Study on the efficacy and safety of the combination of Shi’s manual therapy and percutaneous endoscopic lumbar diskectomy for lumbar disc herniation with radiculopathy: study protocol for a multicenter randomized controlled trial - Wang, Huihao; Yuan, Weian; Yu, Zhongxiang; Wang, Xiang; Zhao, Xinxin; Deng, Zhen; Yang, Guangyue; Chen, Weinan; Shen, Zhibi; Zhan, Hongsheng (Current controlled trials in cardiovascular medicine, 2022)
Lumbar disc herniation (LDH) is a common chronic musculoskeletal disorder that seriously affects quality of life. The percutaneous endoscopic lumbar diskectomy (PELD) technique was developed to address spinal nerve root compression through direct visualization of pathological findings while minimizing tissue destruction upon exposure. It is an effective and safe treatment for LDH. However, recurrent LDH is a major concern after lumbar discectomy for primary LDH. A considerable number of clinical studies have reported that patients with LDH with radiculopathy could benefit from manual therapy. Shi's manual therapy (SMT) was established based on traditional Chinese medicine (TCM) theory and has been shown to have a superior effect in alleviating muscle tension and loosening joints to improve lumbar and leg pain, radiculopathy, stiffness, activity discomfort, and related disorders. However, there is a lack of high-quality clinical evidence to support this conclusion. The purpose of this study is to evaluate the efficacy and safety of the combination of Shi's manual therapy (SMT) and PELD for LDH with radiculopathy. A multicenter randomized controlled trial (RCT) with a 1-year follow-up period will be performed. A total of 510 participants with LDH with radiculopathy will be recruited from four clinical centers. The sample size was estimated, and statistical analysis will be performed and supervised by biostatisticians from an independent third-party research institution. Two hundred fifty-five subjects will be randomly allocated to each group. The subjects in the control group will undergo PELD. Participants in the intervention group will be treated with a combination of SMT and PELD. Recurrence rate is the primary endpoint and the survival analysis of recurrence rate is the secondary endpoint, and the primary analysis of recurrence rate is the chi-square test and the secondary analysis of recurrence rate is survival analysis. The primary outcome measure is the recurrence rate of LDH with radiculopathy at the 1-year follow-up after treatment. The secondary outcome measures will be the ODI score, the VAS score for pain for the lumbar spine and lower limbs, the straight leg raise angle, the stability of the operated lumbar segment, and the SF-36 scores. Assessments will occur at baseline, postoperation, and 1 week, 4 weeks, 13 weeks, 26 weeks, and 1 year postoperation. In addition, adverse events related to clinical symptoms and signs and the results of laboratory tests will be documented during the clinical trials. This study will provide reliable evidence of the effectiveness and safety of the combination of SMT and PELD for LDH with radiculopathy. If the results are favorable, it is expected that patients with LDH with radiculopathy will benefit from this study, and many patients could gain a good alternative treatment for LDH with radiculopathy. China Registered Clinical Trial Registration Center ChiCTR2000036515 . Registered on 13 November 2020.